An Increase of Seawater Temperature Upregulates the Expression of Vibrio parahaemolyticus Virulence Factors Implicated in Adhesion and Biofilm Formation - Billaud, Mélanie; Seneca, François; Tambutté, Eric; Czerucka, Dorota (Frontiers in Microbiology, 2022)
Climate change driven seawater temperature (SWT) increase results in greater abundance and geographical expansion of marine pathogens, among which Vibrio parahaemolyticus (Vp) causes serious economical and health issues. In addition, plastic pollution in ocean constitutes a vector for harmful pathogens dissemination. We investigate the effect of elevated SWT on the expression of genes implicated in adhesion and biofilm formation on abiotic surfaces in the clinical Vp strain RIMD2210633, that expresses hemolysins. Among the genes studied, the multivalent adhesion molecule-7 (MAM-7) and the GlcNAc binding protein A (GpbA) were involved in the adhesion of Vp to abiotic and biotic surfaces, while the type IV pili, the mannose sensitive haemagglutinin (MSHA) and the chitin-regulated pilins (PilA) facilitate attachment and biofilm formation. Data presented here show that at 21°C, Vp is still viable but does no either proliferate nor express the virulence factors studied. Interestingly, at 27°C and as early as 1 hour of incubation, all factors are transiently expressed in free-living bacteria only and even more up-regulated at 31°C. These results clearly show that increased SWT has an important impact on the adhesion properties of free-living Vp to plastic support and thus emphasize the role of climate change in the spread of this pathogenic bacteria.